Conditioning pain stimulation does not affect itch induced by intra-epidermal histamine pricks but aggravates neurogenic inflammation in healthy volunteers. (2nd January 2016) - Andersen, H. H.; Imai, Y.; Petersen, K. K.; Koenig, J.; Elberling, J.; Arendt-Nielsen, L.
Abstract: This study investigated whether itch induced by intra-epidermal histamine is subjected to modulation by a standardized conditioned pain modulation (CPM) paradigm in 24 healthy volunteers. CPM was induced by computer-controlled cuff pressure algometry and histamine was introduced to the volar forearm by skin prick test punctures. Moreover, neurogenic inflammation and wheal reactions induced by histamine and autonomic nervous system responses (heart rate variability and skin conductance) were monitored. CPM did not modulate the intensity of histamine-induced itch suggesting that pruriceptive signaling is not inhibited by pain-recruited endogenous modulation, however, CPM was found to aggravate histamine-induced neurogenic inflammation, likely facilitated by efferent sympathetic fibers.